2007
DOI: 10.1007/s11096-007-9139-6
|View full text |Cite
|
Sign up to set email alerts
|

Use and tolerability of newer antipsychotics and antidepressants: a chart review in a paediatric setting

Abstract: ADRs occurred frequently during first 3 months of treatment with atypical antipsychotics and, to a lesser extent, with SSRIs in children and adolescents. Further investigations are urgently needed to better define the benefit/risk ratio of psychotropic medications in paediatric setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The appropriate use of drugs and population characteristics play a key role in the development of ADEs. However, many patients are inappropriately treated [44][45][46][47][48][49][50][51][52][53] and available evidence indicates that approximately 50% of ADEs are preventable [54,55]. In our study, we found a high rate of avoidable ADEs.…”
Section: Discussionsupporting
confidence: 44%
“…The appropriate use of drugs and population characteristics play a key role in the development of ADEs. However, many patients are inappropriately treated [44][45][46][47][48][49][50][51][52][53] and available evidence indicates that approximately 50% of ADEs are preventable [54,55]. In our study, we found a high rate of avoidable ADEs.…”
Section: Discussionsupporting
confidence: 44%
“…We identified 135 studies (57 new studies after the 2012 report 14 ) meeting our review criteria; of these, 126 (93%) reported on harms (Figure 1). 24 …”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] The increase in FBG and TG could be the result of altered insulin secretion. [ 37 ] SGA treatment may directly affect insulin secretion[ 37 ] through several underlying mechanisms: Increased adipose tissue potentially results in insulin resistance, glucose intolerance, and diabetes, the increase in fatty acids could alter glucose metabolism, or the pancreatic β-cell response is diminished. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%